SOIL FERTILITY STATUS AND POTENTIAL LANDSLIDE DISASTER HAZARDS AT AGRIBUSINESS CENTER IN JUHUT VILLAGE OF PANDEGLANG, BANTEN - Muhlisin Muhlisin (Universitas Sultan Ageng Tirtayasa, 2017)
Juhut village is the agribusiness center of Sheep Integrated Village, as the field laboratory, and the locus of Banten Provincial Innovation System.Many programs provided at the site, ranging from seedlings, funding, and community assistance. However, the environmental conditions that support these activities and the potential for landslides has not been widely studied yet. Therefore, identification of soil fertility status and potential landslides disaster hazard in the Juhut Village needs to be done. The survey was conducted on July-October 2015 by taking soil samples at six locations around Juhut Village: Kadu Salak, Kadu Limus, Canggoang, Cinyurup, Sanim, and Balangendong. Soil samples were analyzed at the Laboratory of Land Resources Research and Development, Ministry Agricultural in Bogor. Potential landslides were analyzed using RBI Map of Indonesia overlied by Google Earth using Watershed Modeling System software, and the category is determined according Kusratmoko (2002). Based on the results of the study note that soil fertility in the Juhut Village of Pandeglang range of low to high. Zoning areas vulnerable to landslides in the area juhut showed mostly a temperate zone with detailed granularity: landslide zonation high, medium, and low respectively covering 245.3, 707.1 and 126.1 hectares. High avalanche zones are located mainly in the central region and the northwest region, which is part slopes of Mount Karang. High avalanche zones are located mainly in the region of Central and Northwest region, which is part slopes of Mount Karang. High landslide zone area is in forest areas, but also there are some places that are on land use mixed garden, farm / field. Efforts need to be done at high risk zone is to increase community capacity by providing The landslide dissaster dissemination and training, and application LEWS (Land Slide Early Warning System). While in the area of agribusiness centers of sheep and goats for a very open area planting perennials.